Green synthesis, characterization and antibacterial study on the catechin-functionalized ZnO nanoclusters - Baihan Zhao; Shixian Deng; Jingchao Li; Congcong Sun; Yujie Fu; Zhiguo Liu (Materials Research Express, 2021)
Green synthesis of zinc oxide nanomaterials has received recent attention due to the potential application of these nanomaterials as biocidal agents to combat antibiotic resistant organisms. In this paper, we provide a facile, one-step hydrothermal approach to prepare catechin-functionalized ZnO nanoclusters in aqueous solution. The obtained ZnO nanoclusters were characterized by UV spectroscopy (UV), Fourier transform infrared spectroscopy (FTIR), transmission electron microscopy (TEM), atomic force microscopy (AFM), x-ray diffraction (XRD) and x-ray photoelectron spectroscopy (XPS). The results of FTIR indicated that the catechin molecules were adsorbed on the surface of ZnO nanoclusters. TEM determination revealed that small ZnO nanoparticles tend to aggregate and form nanocluster structures. Antibacterial activity was tested by paper disk diffusion and the catechin-functionalized ZnO nanoclusters showed high biocidal activity against gram-positive bacteria, gram-negative bacteria and fungi.